2020
DOI: 10.1097/hnp.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Workshops Effects on Nurses' Burnout, Stress, and Mindfulness Skills

Abstract: Burnout decreases work performance and quality of care and can result in medical errors, lower patient satisfaction, and higher rates of turnover. A study of 68 000 registered nurses showed that 35% of hospital nurses were experiencing symptoms of burnout. A systematic review identified that mindfulness-based interventions for health care professionals reduced stress and burnout and increased self-compassion and general health. However, the authors determined that more high-quality research is needed. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 19 publications
8
38
1
Order By: Relevance
“…The mechanism may be as follows: mindfulness can affect cognition, attention and emotional regulation (Hamarta et al., 2013); furthermore, mindfulness is an effective way of decompression through mindful breathing, body scanning, sitting meditation and walking meditation (Ghawadra et al., 2020). Through training, the gradually enhanced mindfulness state can help regulate a person's ability to change cognitive biases and increase positive cognitive reappraisal, enhancing the effective perception of the current state (Elloy et al., 2001) and effectively improving job satisfaction (Abbott et al., 2014; Sarazine et al., 2020; Smith, 2014). However, whether mindfulness intervention can improve male nurses' occupational well‐being has not been explored to date.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism may be as follows: mindfulness can affect cognition, attention and emotional regulation (Hamarta et al., 2013); furthermore, mindfulness is an effective way of decompression through mindful breathing, body scanning, sitting meditation and walking meditation (Ghawadra et al., 2020). Through training, the gradually enhanced mindfulness state can help regulate a person's ability to change cognitive biases and increase positive cognitive reappraisal, enhancing the effective perception of the current state (Elloy et al., 2001) and effectively improving job satisfaction (Abbott et al., 2014; Sarazine et al., 2020; Smith, 2014). However, whether mindfulness intervention can improve male nurses' occupational well‐being has not been explored to date.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, organizations must focus strongly on prevention and mitigation of burnout and related conditions. While many interventions focus on reducing stressors and building resilience (Magtibay et al 2017;Sarazine et al 2020), few focus on improving overall mental well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions of stress and depersonalization improved but were not statistically significant. In this study, nurses reported decreases in burnout and perceived stress and increases in mindfulness after attending a 4-hour mindfulness workshop [20][21][22].…”
Section: Discussionmentioning
confidence: 74%